Automated intraoperative central sulcus localization and somatotopic mapping using median nerve stimulation. (1st August 2022) - Xie, Tao; Wu, Zehan; Schalk, Gerwin; Tong, Yusheng; Vato, Alessandro; Raviv, Nataly; Guo, Qinglong; Ye, Huanpeng; Sheng, Xinjun; Zhu, Xiangyang; Brunner, Peter; Chen, Liang
Abstract: Objective . Accurate identification of functional cortical regions is essential in neurological resection. The central sulcus (CS) is an important landmark that delineates functional cortical regions. Median nerve stimulation (MNS) is a standard procedure to identify the position of the CS intraoperatively. In this paper, we introduce an automated procedure that uses MNS to rapidly localize the CS and create functional somatotopic maps. Approach . We recorded electrocorticographic signals from 13 patients who underwent MNS in the course of an awake craniotomy. We analyzed these signals to develop an automated procedure that determines the location of the CS and that also produces functional somatotopic maps. Main results . The comparison between our automated method and visual inspection performed by the neurosurgeon shows that our procedure has a high sensitivity (89%) in identifying the CS. Further, we found substantial concordance between the functional somatotopic maps generated by our method and passive functional mapping (92% sensitivity). Significance . Our automated MNS-based method can rapidly localize the CS and create functional somatotopic maps without imposing additional burden on the clinical procedure. With additional development and validation, our method may lead to a diagnostic tool that guides neurosurgeons and reduces postoperative morbidity in patients undergoing resective brain surgery.